Designing a Drum Incinerator with a Solar-Powered Air Supply System - Jamrud Aminuddin; Wihantoro Wihantoro; Rostaman Rostaman; Maskhiyatus Shokhib; Ulil Azmi; Dian Rizqi Saputra (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
The growing problem of household waste, along with the practice of open burning, remains a major cause of environmental pollution and public health problems. This study aims to design a simple waste incinerator based on appropriate technology, equipped with a blower system, a water-based smoke filter, and a solar energy source, to improve combustion efficiency and reduce smoke emissions. The research was conducted using an engineering research approach, involving literature studies, observations, and conceptual design, without fabrication or direct experimental testing. The device was designed with an iron drum as the main combustion chamber, an input blower to increase oxygen supply during combustion, and an output blower to direct smoke toward a water-based filtration system (a simple wet scrubber). The blower system uses DC power supplied by solar panels and batteries, allowing the device to operate independently and efficiently. The study results indicate that the use of blowers can improve flame stability, accelerate combustion, and reduce smoke from incomplete combustion. In addition, the water-based filtration system is considered simple, economical, and sufficiently effective in trapping dust particles and fine ash before the smoke is released into the environment. This device is specifically designed to burn lightweight organic waste such as dry leaves, small branches, and paper, making it suitable for household and community-scale applications. This research is expected to serve as a basis for developing a simpler, more economical, easy-to-apply, and environmentally friendly waste incinerator as an alternative community-based waste management solution.